Impactos do EDI e da Internet na logística de empresas da indústria de alimentos - Ferreira, Karine Araújo (2005)
Operations management in the global economy has induced food industry s companies to promote a productive reorganization which can be verified by the technological, organizational and commercial changes in their activities. The adoption of integrated logistics contributes to cost reduction and flexibility gains in means of outputs production and circulation. Information sharing amongst companies and their business partners makes possible the coordination of new forms of relationships and their efficient logistical management. Several information and communication technologies have presented wide use in logistics, such as the Electronic Data Interchange (EDI) and the Internet, both being analyzed in this work. These technologies support the decisionmaking process of technical and organizational relationships between the productive actors, through fast and form-requested information exchange. The objective of this dissertation is to investigate the impacts carried through EDI and Internet s usage as a follow-up framework related to the performance and organization of sweet-foodprocessing companies logistical activities, aiming the electronic information exchange with their partners of the immediate chain. Nevertheless, three logistical activities are evaluated in this work: transport, inventory management and order processing; being the first two responsible for logistics cost and the last one representing the most timeconsuming activity in order cycles. The theoretical basis of this analysis was encrusted with bibliographical revisions of related subjects, such as: Logistics, Information System, Communication and Information Technology, EDI, Internet and Food Industry. The empirical research was carried through three case-studies within the candy food s companies. The results shed light on how the logistical activities are organized into companies supplying and physical distribution areas, as well as the reasons and willingness for EDI and Internet s adoption on certain activities and their overall benefits. Several results from using electronic information exchange to coordinate and improve logistics activities were verified, such as: better knowledge of transport planning and vehicles programming; better inventory visibility; greater agility in the reception and order processing; errors, cycle time and additional freights reduction.